The treatment of skin ulcers in patients with systemic sclerosis - M. Matucci- Cerinic; F. Braschi; A. Moggi Pignone; L. Amanzi; G. Fiori (PAGEPress Publications, 2011)
Systemic Sclerosis (Ssc) is a complex disease of the connective tissue, characterized by progressive thickening and fibrosis of the skin and the internal organs and by diffused damage of the microvascular system. The fibrosis ones of the skin associated to the characteristic vascular alterations lead to the genesis of ulcers, more or less extended, often multiple, peripheral localization, chronic course, painful, able to influence patient's quality of life. Indeed, immunity reactivity, the thinning and the loss of elasticity of the skin, the peripheral neurological damage and the eventual drug assumption that can reduce regenerative/reparative abilities, can easy chronicizzate an ulcer and become infected complicating still more the patient disease, rendering more difficult the cure often, ulcer evolves to gangrene, and in some cases, in amputation too. For all these reasons, we have begun to study ulcers therapy (local and systemic), considering this activity it leave integrating of the charitable distance of the sclerodermico patient, putting to point on strategy both diagnostic and therapeutic, but above all with the primary scope, if possible, is to prevent ulcers, in contrary case, to alleviate the pain and to render the quality of the life of the patient better.